Strengthening Healthcare through Academic and Industry Partnership Research - Sathian, Brijesh; van Teijlingen, Edwin; Simkhada, Padam; Banerjee, Indrajit; Manikyam, Hemanth Kumar; Kabir, Russell (Nepal Journal of Epidemiology, 2023)
Academic and Industry Partnership Research Grants have a huge potential to improve healthcare in the UK and elsewhere. This potent partnership between academia and business can hasten medical innovation, strengthen patient-centered research, and close the gap between theoretical understanding and real-world implementations. We can make sure that the quest of scientific knowledge continues to be at the forefront of healthcare developments by welcoming this partnership while respecting ethical norms and transparency. The UK's dedication to developing long-term alliances based on mutual respect and open dialogue will help create a climate in which ground-breaking research may flourish and be transformed into affordable healthcare solutions.